2009
DOI: 10.1111/j.1439-0523.2008.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐ray radiation induced dwarf mutants of turf‐type bermudagrass

Abstract: To generate new breed lines of bermudagrass and reduce management costs of turfgrass, gamma-ray irradiation was used for induction of dwarf mutants from a native bermudagrass (Cynodon dactylon) germplasm. Three dwarf-type mutant lines (7-9, 10-5 and 10-12) were isolated from 3000 irradiated stolons. The data from 3-year greenhouse tests and 2-year field tests indicated that the dwarf mutant lines had lower canopy height, shorter internodes and shorter leaves. The line 7-9 had a similar turf coverage rate to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…Similar results were reported with other species of Poaceae family (Busey, 1980;Krishna et al, 1984;Hase et al, 1999;Zaka et al, 2002). Results showed that gamma irradiation doses of 70 to 113 Gy were successful in creating bermudagrass mutants, concurring with earlier reports (Powel et al, 1974;Burton, 1985;Hanna et al, 1997b;Caetano-Anolles, 1999;Hanna and Elsner, 1999;Lu et al, 2009 Lu et al, (2009) and (Li et al, 2010), respectively. Dwarfisms have been associated with defection in biosynthesis or reception of gibberellins (Ross et al 1997), brassinosteroids (Noguchi et al 1999), and regulation of cell elongation (Takahashi et al 1995) or with abnormal cell walls (Reiter et al, 1993).…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were reported with other species of Poaceae family (Busey, 1980;Krishna et al, 1984;Hase et al, 1999;Zaka et al, 2002). Results showed that gamma irradiation doses of 70 to 113 Gy were successful in creating bermudagrass mutants, concurring with earlier reports (Powel et al, 1974;Burton, 1985;Hanna et al, 1997b;Caetano-Anolles, 1999;Hanna and Elsner, 1999;Lu et al, 2009 Lu et al, (2009) and (Li et al, 2010), respectively. Dwarfisms have been associated with defection in biosynthesis or reception of gibberellins (Ross et al 1997), brassinosteroids (Noguchi et al 1999), and regulation of cell elongation (Takahashi et al 1995) or with abnormal cell walls (Reiter et al, 1993).…”
Section: Discussionsupporting
confidence: 82%
“…In total, of the 4301 treated stolon cuttings, 15 morphological mutants (0.35% of the irradiated plants) with a semidwarfed growth habit were identified. Similar to our results, the useful mutant rates were 0.3% in Raleigh St. Augustinegrass (Li et al, 2010) and bermudagrass (Lu et al, 2009; Sever Mutlu et al, 2015). The practical doses for the two genotypes were 40 and 50 Gy.…”
Section: Resultssupporting
confidence: 90%
“…2 and 3). Similar reductions were reported in Raleigh St. Augustinegrass (36-48%) (Li et al, 2010), bermudagrass (50-55%) (Lu et al, 2009), and in other species of grass family (31-84%) (Cheema and Atta, 2003;Al-Salhi et al, 2004;Borzouei et al, 2010;Nasab et al, 2010;Kim et al, 2015). Dwarfisms have been associated with defection in biosynthesis or reception of gibberellins (Phinney, 1985;Ross et al, 1997), brassinosteroids (Noguchi et al, 1999), and regulation of cell elongation (Takahashi et al, 1995) or with abnormal cell walls (Reiter et al, 1993).…”
Section: Resultssupporting
confidence: 78%
“…By itself, dwarfism can be a highly desirable trait for turfgrass because dwarf cultivars require less frequent mowing and can therefore reduce costs associated with lawn maintenance ( Johnson, 1994 ). There are other beneficial phenotypes associated with dwarfism in turfgrass, such as drought tolerance ( Lu et al, 2009 ). Additionally, we have reported that, in perennial ryegrass, prostrate growth can be a beneficial secondary phenotype associated with dwarfism ( Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that many dwarf mutants are dominant or semi-dominant ( Busov et al, 2008 ). Dwarfism itself is an important trait for perennial ryegrass, as it can reduce costs associated with mowing, irrigation, and fertilization ( Hanna and Elsner, 1999 ; Lu et al, 2008 , 2009 ). Other beneficial traits, such as prostrate growth, are also associated with dwarfism in perennial ryegrass ( Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%